Role of the ubiquitin-proteasome system in the sarcopenic-like phenotype induced by CCL5/RANTES - Sabrina Conejeros-Lillo; Francisco Aguirre; Daniel Cabrera; Felipe Simon; Luis Peñailillo; Claudio Cabello-Verrugio (European Journal of Translational Myology, 2024)
Sarcopenia is characterized by reduced muscle strength and mass and a decline in muscle fiber diameter and amount of sarcomeric proteins. Sarcopenia involves the activation of the ubiquitin-proteasome system (UPS). MuRF-1 and atrogin-1 are E3 ubiquitin ligases belonging to UPS, leading to proteolysis mediated by the PSMB 5, 6, and 7 subunits of 20S proteasome. CCL5/RANTES induces a sarcopenic-like effect in muscle cells. The present work explored the impact of CCL5 on UPS components and the influence of UPS on its sarcopenic-like effect. We demonstrated that CCL5 increased MuRF-1 and atrogin-1 protein levels and mRNA levels of subunits PSMB 5, 6, and 7. We used the MG132 inhibitor to elucidate the role of the 20S proteasome in the CCL5-induced sarcopenic-like effect. This inhibitor prevented the decrease in troponin and MHC protein levels and partially prevented the reduction in the diameter of single-isolated FDB muscle fibers induced by CCL5. These findings indicate that CCL5 actively modulates the UPS. Moreover, our results show the direct participation of UPS in the sarcopenic-like phenotype induced by CCL5.